Unconfined Compressive Strength Of Sedimentary Soil Stabilized With Portland Cement With Varying Curing Time - Nursamiah, Nursamiah; Fattah, Abdul; Fahmi, Rizky Hadijah (Politeknik Negeri Ujung Pandang, 2022)
Soil improvement is commonly carried out in construction work with the aim of increasing the bearing capacity / strength of the soil so that it can carry the construction load that will stand on it. The method that is often used is soil stabilization with the addition of stabilization materials. In this study, soil stabilization was carried out with the addition of Portland Cement. This research begins with soil sampling and laboratory testing to determine the physical and mechanical properties of the soil, followed by making soil samples for Unconfined compressive strength testing with 3 variations of cement, namely 5%, 10%, and 20%. From the results of this study, it is known that the soil sample has a moisture content of 97.13%, specific gravity of 2.51, liquid limit of 33.80% and plasticity limit of 22.52% with plastic index value = 11.28%. Based on the soil classification system with the USCS (Unified Soil Classification System) method, sedimentary soil types include CL (Clay-Low) soil types, clays with low plasticity values. Unconfined compressive strength testing on sedimentary soil samples without portland cement obtained a compressive strength value of 0.352 kg/cm2. And the soil stabilized with various variations of Portland Cement obtained the highest compressive strength value of 14.45 kg/cm2, namely in the soil sample + 20% cement with 28 days curing time. The results showed that the value of Unconfined compressive strength for sedimentary soil dredging dam bili-bili stabilized with Portland cement tends to increase its bearing capacity / strength with the addition of the percentage of Portland cement and curing time, with this value the category of hard soil consistency obtained can be used for building structures and road base soils.